2012
DOI: 10.5402/2012/204624
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Staged Preconditioning on Biochemical Markers in the Patients Undergoing Coronary Artery Bypass Grafting

Abstract: The present study has investigated the effectiveness of staged-preconditioning, in both remote and target organs. After IP the myocardial release of the biochemical markers including, creatine phosphokinase (CPK), cardiac creatine kinase (CK-MB), cardiac troponin T (cTnT) and lactate dehydrogenase (LDH) were evaluated in patients who underwent CABG, with and without staged-preconditioning. Sixty-one patients entered the study; there were 32 patients in the staged-preconditioning group and 29 patients in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…A previous study with not well-described pulsatile perfusion method showed that the LDH levels at 48 and 72 h after operation were significantly higher in the non-pulsatile perfusion, which needs further considerations. 25 Although controversial, the degree of organ injuries, mainly liver and kidney, seem similar in our investigated patients. Therefore, we suppose that nonpulsatile flow could be applied confidently in selected patient populations.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A previous study with not well-described pulsatile perfusion method showed that the LDH levels at 48 and 72 h after operation were significantly higher in the non-pulsatile perfusion, which needs further considerations. 25 Although controversial, the degree of organ injuries, mainly liver and kidney, seem similar in our investigated patients. Therefore, we suppose that nonpulsatile flow could be applied confidently in selected patient populations.…”
Section: Discussionmentioning
confidence: 60%
“…A previous study with not well-described pulsatile perfusion method showed that the LDH levels at 48 and 72 h after operation were significantly higher in the non-pulsatile perfusion, which needs further considerations. 25…”
Section: Discussionmentioning
confidence: 99%
“…CPB can cause body organ malperfusion and dysfunction (17)(18)(19). Loss of pulsatility of pump flow is one of the items which may be responsible for organ malperfusion (20,21) and worse blood microcirculation (11,22). It is still controversial whether maintaining pulsatile flow is associated with less end-organ damage or not (23,24).…”
Section: Discussionmentioning
confidence: 99%